PERCEPTION TOURIST TO PROMOTION OF PADANG BEACH WEST SUMATERA PROVINCE - Rahmat Rizki; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research is to know the perception tourism to promotion of Padang Beach West Sumatera Proince. This Study aim: (1) How the perception tourist to promotion of Padang Beach. This research uses quantitative method woth descriptive approach, the research subjects are tourist visitting Padang Beach,Tourism Depatement Of PadangCity. The sample used in this research is 100 people. Data collection is done by observation, questionnaire, documentation. The data analysis used in this study is based on facts found in the field through the results of questionnaires, and with conclusions. Based on the results of research that has been done, the perception of tourist to the promotion of Padang Beach West Sumatera Province influenced by various promotions, such as advertising promotion, public relations promotion, mouth of mouth promotion, sales promotion. The conclusion of the most dominant promotion in the perception tourist to the promotion Padang Beach of West Sumatera Province is the promotion of advertisingand the most dominant indicator is the promotion of public relations in the form of holding events. Keywords: Perception, Tourist, Promotion